(untitled) (Fiep Bulletin - online, 2013)
The gynecological age can be an important resource to evaluate the somatic and motor development in the period powder-menarca. This way, the objective of this study was to evaluate the relationship of the gynecological age with variables anthropometrics and pubescent no-athletes’ basic physical qualities. The sample consisted of 164 young females with age among 10 and 16 years that obeyed the inclusion criteria. The date of the menarca and the chronological age were obtained through an anamnesis, making possible the calculation of the gynecological age. The variables anthrpometrics in study were the body mass, stature, body mass index (BMI), fat percentage, thin mass, fat mass and components of the somatotype. The basic physical qualities were the explosive force of inferior members, velocity and VO2máx. The average and the standard deviation were used to describe the data, following by the correlation of Pearson to identify which varied if they relate with the gynecological age. Positive and significant correlations (p <0,01) they were found in the variables body mass, BMI, fat percentage, thin mass, fat mass, endomorphy, mesomorphy and explosive force of inferior members. Negative and significant correlations (p <0,01) they were found in the variables ectomorphy and VO2máx. It is ended that in the period post menarche there is the tendency of increase of the body mass, BMI, fat percentage, thin mass, fat mass, endomorphy, mesomorphy and explosive force of inferior members; a tendency of decline of the ectomorfia and of relative VO2máx; not having significant alterations in the stature and speed.